Efficient conversion of solar energy through a macroporous ceramic receiver coupling heat transfer and thermochemical reactions. (15th May 2023) - Guene Lougou, Bachirou; Wu, Lianxuan; Ma, Danni; Geng, Boxi; Jiang, Boshu; Han, Donmei; Zhang, Hao; Łapka, Piotr; Shuai, Yong
Abstract: The receiver/reactor engineering and radiative power distribution technology are still challenging the development and rapid upscaling of solar thermal conversion and storage processes. This study dealt with experimental investigations of thermochemical CO2 -splitting process and systematically provided pioneer approaches for efficient conversion of solar energy through complex coupled numerical models of reactor and high-flux solar simulator. The radiative heat transport of high-flux concentrated solar energy throughout the macroporous reactor is performed considering the fluid flow and heat transfer phenomena. The system performance is demonstrated through experimental measurements combining numerical analysis. The thermal efficiency of the reactor is mainly influenced by the cavity wall insulation thermal conductivity, wall thickness, and cavity configuration. Most thermal losses along the receiver are localized at the fluid-solid heat flux transiting phases. Modifying the internal structure of the receiver, such as removing the aperture and further improving the model by hollowing the porous media, could induce 20% solar-to-thermal processing performance increment with higher temperature distribution using a cavity wall having thermal conductivity of 0.3 W/m·K. Beyond the experimental observations, the numerical analysis provided new insights into the solar receiver/reactor innovation strategy and redox material composition selectivity. Highlights: Solar energy efficient conversion is assessed via experiments and numerical analysis. Effects of cavity configuration, wall thermal conductivity, and thickness are studied. Coating oxide materials to SiC substrate improve light-to-heat conversion. Experimental results showed promising thermochemical CO2 conversion performance. Solar-thermal performance rises to 20% by improving incoming radiative flux absorption.